Association between Prepartum Feeding Behavior and Periparturient Health Disorders in Dairy Cows - Luchterhand, Karen M.; Silva, Paula R. B.; Chebel, Ricardo C.; Endres, Marcia I. (Frontiers in Veterinary Science, 2016)
The objective of this study was to investigate the relationship between prepartum feeding behaviour, measured as time spent feeding per day, and periparturient health disorders, milk yield, milk composition, and milk somatic cell count in Jersey cows. Pregnant Jersey cows were marked with unique alphanumeric symbols and were moved into a prepartum group four weeks prior to their expected calving date. At enrollment, cows with a body condition score < 2 or > 4 or a locomotion score > 3 were not included. Time spent feeding was measured using 10-min video scan sampling for 24-hour periods 2 to 4 days per week of the study. A total of 925 cows were eligible for analysis. Parity was based on lactation number at time of enrollment and classified as nulliparous (cows pregnant with their first calf), primiparous (cows pregnant with their second calf) and multiparous (lactation > 2). Multiparous cows with two or more health disorders spent approximately 10% less time feeding prepartum than cows that did not have any health disorders. Multiparous cows subsequently diagnosed with metritis had a tendency to spend 5% less time feeding prepartum than healthy counterparts. Primiparous cows with retained placenta had a 10% reduction in feeding time compared to healthy primiparous cows. Monitoring time spent feeding prepartum by primiparous and multiparous cows, even on a limited number of days, appeared to be beneficial in predicting cows at risk for periparturient health disorders. Real-time daily feeding behaviour monitoring technologies that can be used by dairy farms are now available which might prove to be even more helpful in identifying cows at risk for periparturient cow health disorders as more data points can be recorded for each cow and compared to her own behaviour or that of specific cohorts.